Viewing Activities through Video Based on Emancipated Curriculum for Senior High School Students - Alifiardi Aditya Maulana Rahman (Universitas Negeri Surabaya, 2025)
Viewing Skill is a recent language skill that involves visual media. This study aims to examine the implementation of learning and the results of student worksheets when viewing skills are applied. This qualitative descriptive study, conducted through classroom observations, involves one teacher and 33 out of 42 students from class 11. The findings show that (1) the implementation of viewing skills in the learning activities has been effective based on the observations made, but improvements are needed in the execution of viewing skills instruction, (2) the students' learning outcomes after the application of viewing skills indicate that students perform better when answering questions with the help of visual aids, such as images. The researcher recommended combining viewing skills with methods that foster critical or analytical thinking. Teachers were encouraged to use visual media, such as relevant educational videos and films, and integrate viewing skills with activities like discussions or writing to enhance the learning process.